RESPONSIBILITY TO PROTECT PRINCIPLE CONSTRUCTION ON INTERNATIONAL AND NATIONAL LEVELS: CASES OF THE UN AND THE USA - Lokė, Brigita (Politologija, 2016)
Responsibility to protect is a very controversial principle in the international arena. One group of researchers name it the new approach and impulse for human security and human rights improvements with deeper involvement and response from the international community. On the contrary, other group of researchers state that this concept doesn’t bring any new insights for situation improvement and can even be harmful, because it may, in some way, give a better opportunity for justification of the country’s unilateral intervention. While discussion is still ongoing, the rising and concerning issue is how this concept (let it be remembered that this is the product of a special committee outside the United Nations (UN)) is evolving and fixating itself on the international and national level – as prioritizing one country humanitarian actions or the joint response from international community. To analyse this issue, the UN is taken as the most important international actor regarding the question of international peace and security. USA is taken to analyse it from the national level. The research is based on primary source analysis. Results of the UN documents and primary source analysis indicate that the concept of responsibility to protect this organisation is evolving gradually. First, it was started with the basic and uncontroversial assumptions from the concept, then the idea of the possible fruitful cooperation with other regional and transnational organisations was introduced. Furthermore, the required steps before and after the crisis are named, strictly defined cases when responsibility to protect principle can be applied. In the UN, the principle is developing in more narrow in comparison with the primal guidelines from the special committee. Organisation clearly defines that the principle of responsibility to protect can be used just by the international community with the mandate of UN Security Council. No other options for other organisations or state are declared, even in the cases when the UN Security council is not able to take appropriate actions. With some exceptions, the analysis supports the researchers’ claim that international actions are prioritised and not very specific issues are added by this principle. Regarding the position of the USA, the result estimates a very incoherent position. In various sources, the position changes from very unfavourable to favourable. One of the most opposing statements from the responsibility to protect statement for US is the obligation to act in the situations where human rights condition is in a very poor situation. This is seen as framing countries actions; for this reason, there is an intention to change it to readiness to act. Considering the time frame of written sources, it can be seen that the position is changing to more favourable towards the responsibility to protect the concept itself, but to clearly define that position – one country’s humanitarian intervention or international response – is very difficult because the stated position is very ambiguous.